MicroRNA221-3p modulates Ets-1 expression in synovial fibroblasts from patients with osteoarthritis of temporomandibular joint. Issue 11 (November 2016) - Xu, J.; Liu, Y.; Deng, M.; Li, J.; Cai, H.; Meng, Q.; Fang, W.; Long, X.; Ke, J.
Summary: Objective: This study aimed to screen differential expression of microRNAs (miRNAs), and investigate function of the specifically selected miRNA in synovial fibroblasts from patients suffering osteoarthritis of temporomandibular joint (TMJOA). Methods: MiRNA microarray was used to select differentially expressed miRNAs between TMJOA and normal synovial fibroblasts. The expression of screened miRNA221-3p was quantified using real-time PCR, and its specific target gene was predicted by bioinformatics. After transfection of miRNA221-3p mimics or inhibitor into synovial fibroblasts, the expression of v-Ets avian erythroblastosis virus E26 oncogene homolog 1 (Ets-1) was detected by immunohistochemistry, real-time PCR and Western blot, respectively. Dual luciferase activity was performed to identify the direct regulation of miRNA221-3p on Ets-1. Interlukin-1β (IL-1β) mimics an inflammatory situation. Results: In TMJOA synovial fibroblasts, eight miRNAs were up-regulated and six miRNAs were down-regulated. MiRNA221-3p was the most down-expressed. A sequence in the 3′-untranslated (3′-UTR) of Ets-1 complementary to the seed sequence of miRNA221-3p. Elevated expression of Ets-1 associated with attenuation of miRNA221-3p. Over-expression of miRNA221-3p suppressed the activity of a reporter construct containing the 3′-UTR of Ets-1 transcript and inhibited the expression of Ets-1 as well as its downstream molecules, matrix metalloproteinase 1 (MMP1) and MMP9 in TMJOA synovial fibroblasts. IL-1β suppressed the expression of miRNA221-3p in both a dose-dependent and time-dependent manner. Conclusion: The reduction of miRNA221-3p in synovial fibroblasts, attributed from abundance of IL-1β in inflamed circumstance, induces Ets-1 up-regulation and then, initiates MMP1 and MMP9 secretion, thereby leading to continuously pathological development in TMJOA.